Judging from experience : law, praxis, humanities - Gaakeer, A. M. P. (Edinburgh : Edinburgh University Press, 2019)
Combining her expertise in legal theory and judicial practice in a continental-European civil-law system, Jeanne Gaakeer explores the intertwinement of legal theory and practice to develop a humanities-inspired methodology for both the academic interdisciplinary study of law and literature and for legal practice.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 14, 2019).
Keywords: Law -- Philosophy; Practice of law -- Philosophy; Law; Jurisprudence & general issues